Impact of Breakfast Skipping and Choices on The Nutrient Intake and BMI of University Hostel Students of Lahore - Zulfiqar, Maryam; Shahbaz, Hafiz Muhammad; Ikram, Iqra; Ahmed, Waqas; Rehman, Abdul (Indonesian Food and Nutrition Progress, 2024)
This longitudinal study aimed to investigate the food choices of university hostel students and explore the relationship between breakfast skipping, food choices, nutrient intake, and BMI. Data were collected from students residing in university hostels over a three-month period, with monthly assessments. The study included 306 students divided into breakfastskippers and breakfast-eaters (control group), each comprising 153 students. Further categorization was performed among the breakfast eaters. A valid assessment questionnaire was used, encompassing social demographic characteristics, anthropometric measures, lifestyle assessment, dietary assessment through 24-hour dietary recall, and food composition table analysis. Among breakfast skippers, 15% were classified as obese and 13.7% as overweight, which was higher compared to other groups. Among the non-cereal-based breakfast eaters, 14.4% were obese, and 21% were overweight. The cereal-based breakfast eaters had the lowest rates of obesity and overweight, with 6.4% falling into each category. Significant differences were observed in calorie consumption and the intake of micronutrients across different breakfast categories. This study provided strong evidence linking breakfast skipping to a higher BMI (26.2 vs 24.1) and age-related patterns, with more breakfast skippers among younger individuals. Non-cereal-based breakfasts had a superior nutrient intake, while breakfast skippers had more screen time and insufficient sleep. Emotional states as triggers for binge eating were reported